'Regenerating community'? Urban change and narratives of the past. Issue 4 (7th September 2016) - Lewis, Camilla
Abstract: This paper explores how understandings of community and belonging have shifted in relation to rapid deindustrialization and subsequent waves of redevelopment in East Manchester. Drawing on ethnographic research, it focuses on two social settings which are under threat of closure – a coffee morning and a market place. In these settings, long‐standing residents make community, paradoxically, by sharing narratives about the loss of social ties. Drawing on relational approaches to place, the discussion sheds light on the disruption between place and identity in post‐industrial localities which have been reshaped by drastic physical regeneration. The paper argues that in order to understand the apparent contradiction between narratives of social decline and observations of abundant social relations, it is necessary to extend existing sociological and anthropological approaches to community and belonging.